Data from: Altitude effects on spatial components of vascular plant diversity in a subarctic mountain tundra ... - Naud, Lucy; Måsviken, Johannes; Freire, Susana; Angerbjörn, Anders; Dalén, Love; Dalerum, Fredrik (Dryad, 2019)
Environmental gradients are caused by gradual changes in abiotic factors, which affect species abundances and distributions, and are important for the spatial distribution of biodiversity. One prominent environmental gradient is the altitude gradient. Understanding ecological processes associated with altitude gradients may help us to understand the possible effects climate change could have on species communities. We quantified vegetation cover, species richness, species evenness, beta diversity, and spatial patterns of community structure of vascular plants along altitude gradients in a subarctic mountain tundra in northern Sweden. Vascular plant cover and plant species richness showed unimodal relationships with altitude. However, species evenness did not change with altitude, suggesting that no individual species became dominant when species richness declined. Beta diversity also showed a unimodal relationship with altitude, but only for an intermediate spatial scale of 1 km. A lack of relationships with ... : Naud-et-al-DataRaw data for Naud et al. Ecology and evolution. File includes a data table containing % vegetation cover, plant species richness, plant Shannon evenness, and three distances to centroids (which have been used as measurements of beta diversity on three different spatial scales), as well as a binary presence - absence matrix used for community structure calculations. ...